Screening tomato (Lycopersicon esculentum Mill.) Accessions for resistance to the twospotted spider mite tetranychus urticae Koch: Population growth studies - Knapp, Markus; Mugada, Debora Apiyo; Agong', Stephen G. (International Journal of Tropical Insect Science, 2011)
The resistance of 63 tomato (Lycopersicon esculentum Mill.) accessions to the twospotted spider mite Tetranychus urticae Koch (Acari: Tetranychidae), was investigated in screen house experiments and compared to Money Maker, a T. urticae-susceptible variety widely grown in Kenya. The number of motile mite stages 12 days after inoculation with 5 adult female mites was significantly lower than in the control variety (Money Maker) in seven accessions (Marglobe, Roma-VF, 94 RT 330, Continental Michel, Early Pearson, ARP 366–4 and 94 RT 316). Egg numbers were significantly lower than in the control in 14 accessions (Marglobe, Cal-J-VF, Roma-VF, Beauty, 95 RT 315, 93 KT 20, EC.3504,94 RT 313, EC-1193, Continental Michel, Early Pearson, ARP 366–4,94 RT 316 and Malawi Local 3). This study reveals the existence of resistance to T. urticae in the tomato accessions.